Reference and Description : The Case against Two-Dimensionalism - Soames, Scott (Book collections on Project MUSE., 2007)
In this book, Scott Soames defends the revolution in philosophy led by Saul Kripke, Hilary Putnam, and David Kaplan against attack from those wishing to revive descriptivism in the philosophy of language, internalism in the philosophy of mind, and conceptualism in the foundations of modality. Soames explains how, in the last twenty-five years, this attack on the anti-descriptivist revolution has coalesced around a technical development called two-dimensional modal logic that seeks to reinterpret the Kripkean categories of the necessary aposteriori and the contingent apriori in ways that drain.